Characteristics of loads during the catch motion in clean exercise: A comparison with the pull phase - Hayashi, R.; Kariyama, Y.; Yoshida, T.; Zushi, K. (Japan Journal of Physical Education, Health and Sport Sciences, 2016)
The purpose of this study was to identify the ground reaction force and joint kinetics in the lower extremity during the catch phase of the clean exercise through comparison with the pull phase. Eleven male track and field athletes performed the power clean from the floor with loads of 30%, 60%, and 90% of 1RM (One Repetition Maximum). Kinetic data were collected from data recorded using a Vicon motion system (250 Hz) and force platforms (1,000 Hz). The results of the analyses were as follows: 1) In the catch phase, force development was similar to that of the pull phase because the peak ground reaction force was not significant during the 2 phases. 2) The joint kinetics in the ankle and knee joints were larger during the catch phase than during the pull phase. 3) During the power clean, force development was achieved mainly by concentric muscle contraction during the pull phase and by eccentric muscle contraction during the catch phase. 4) The ground reaction force and joint kinetics were significantly different during the catch phase. These results show the differences in load characteristics in the lower extremity between the pull and catch phases during clean exercise. Therefore, not only the pull phase but also the catch phase should be considered when performing the clean exercise in weight training.